Identification of Autophagy-Related LncRNA to Predict the Prognosis of Colorectal Cancer - Duan, Ling; Xia, Yang; Li, Chunmei; Lan, Ning; Hou, Xiaoming (Frontiers in Genetics, 2022)
Objective: To establish a prediction model based on autophagy-related lncRNAs and investigate the functional enrichment of autophagy-related lncRNAs in colorectal cancer. Methods: TCGA database was used to extract the transcriptome data and clinical features of colorectal cancer patients. HADb was used to obtain autophagy-related genes. Pearson correlation analysis was performed to identify autophagy-related lncRNAs. The autophagy-related lncRNAs with prognostic values were selected. Based on the selected lncRNAs, the risk score model and nomogram were constructed respectively. Calibration curve, concordance index, and ROC curve were performed to evaluate the predictive efficacy of the prediction model. GSEA was performed to figure out the functional enrichment of autophagy-related lncRNAs. Results: A total of 13413 lncRNAs and 938 autophagy-related genes were obtained. 709 autophagy-related genes were identified in colon cancer tissues. 11 autophagy-related lncRNAs (AL138756.1, LINC01063, CD27-AS1, LINC00957, EIF3J-DT, LINC02474, SNHG16, AC105219.1, AC068580.3, LINC02381, LINC01011) were finally selected and set as the prognosis-related lncRNAs. According to the risk score, patients were divided into the high-risk and low-risk groups respectively. The survival K-M (Kaplan-Meier) curve showed the low-risk group exhibit better overall survival than the high-risk group. The AUCs under the ROC curves were 0.72, 0.814, and 0.83 at 1-, 3- and 5-years respectively. The C-index (concordance index) of the model was 0.814. The calibration curves at 1-, 3- and 5-years showed the predicting values were consistent with the actual values. Functional enrichment analysis showed that the autophagy-related lncRNAs were enriched in several pathways. Conclusions: Eleven specific autophagy-related lncRNAs were identified to own prognostic value in colon cancer. The predicting model based on the lncRNAs and clinical features can effectively predict the OS. Furthermore, functional enrichment analysis showed that autophagy-related genes were enriched in various biological pathways.